2020
DOI: 10.1007/s00415-020-10123-y
|View full text |Cite
|
Sign up to set email alerts
|

Neurological comorbidity and severity of COVID-19

Abstract: Objective Neurological symptoms of COVID-19 patients have been recently described. However, no comprehensive data have been reported on pre-existing neurological comorbidities and COVID-19. This study aims at evaluating the prevalence of neurological comorbidities, and their association with COVID-19 severity. Methods We evaluated all consecutive patients admitted to the Emergency Room (ER) of our hospital between the 3rd March and the 14th April 2020, and diagnosed with COVID-19. Data on neurological and non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 27 publications
2
42
0
1
Order By: Relevance
“…Severe disease. Ten studies reported severe disease as an outcome in COVID-19 patients (19,(54)(55)(56)(57)(58)(59)(60)(61)(62). The definition of severe disease, however, varied among studies.…”
Section: Resultsmentioning
confidence: 99%
“…Severe disease. Ten studies reported severe disease as an outcome in COVID-19 patients (19,(54)(55)(56)(57)(58)(59)(60)(61)(62). The definition of severe disease, however, varied among studies.…”
Section: Resultsmentioning
confidence: 99%
“…After the initial screening, 158 were excluded for not meeting the inclusion criteria, leaving 75 articles to assess for eligibility. After evaluation of the full-text articles, eight met the inclusion criteria 3,4,[11][12][13][14][15][16][17][18][19] and were thus included into the final analysis ( Figure 1).…”
Section: Search Results and Included Studiesmentioning
confidence: 99%
“…1 Over the first 6 months of 2020, several risk factors have been associated with a poor prognosis among COVID- 19 patients, including preexisting neurological disease and advanced age. 2,[3][4][5][6] It should be underscored that, despite dementia represents a common clinical condition, affecting up to 7% of elderly subjects worldwide 7,8 only a few attentions have been posed by medical research on the impact of this disease in elderly COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 423 patients with severe COVID-19, 20 (4.7%) had preexisting neurological comorbidities, with cerebrovascular disease (8 patients) being the most common. Preexisting cerebrovascular disease has been associated with a more severe form of COVID-19 and an increased risk of invasive mechanical ventilation and death [ 11 , 12 ]. Poliomyelitis was the second most common neurological comorbidity associated with severe COVID-19 (4 patients).…”
Section: Neurological Comorbidities and Neurological Symptoms Associamentioning
confidence: 99%